Identifikasi Hama Kutu Putih Pada Bibit Sengon (Falcataria moluccana (Miq.) Barneby And J.W Grimes) Di Persemaian Puslitbang Kehutanan - Yeni Nuraeni; Illa Anggraeni; Neo Endra Lelana (Faculty of Agriculture, Pattimura University, 2016)
Commercial and community plantation of sengon commonly know as Moluccan albizia (Falcataria moluccana (Miq.) Barneby and J.W Grimes) requires qualified transplant, but the supply of such transplant seed is constrained by mealybug pest attack in the nursery. The purpose of this study is to identify the mealybug species that attack Moluccan albizia seeds. Observation of the symptoms mealybug attack in the nursery and identification of mealybug species has been performed in the nursery of Forest Research Center, Bogor. The results were mealybug that attack nursery was Ferrisia virgata belong to the famili Pseudococcidae, the Order Hemiptera. White mealybug colonized the stems and leaves of seeds. The leaves fall and plant wilted when the attack become serous. Predator Curinus coerulus and Coccinella repanda was suggested to be used to control mealybug.